Older People's Neighborhood Perceptions Are Related to Social and Emotional Loneliness and Mediated by Social Network Type. (12th June 2022) - Stephens, Christine; Phillips, Hannah
Abstract: Background and Objectives: Loneliness among older people is a public health issue; however, there is very weak support for the efficacy of individually focused interventions. A public health model, which includes the environmental influence on the formation of social networks and protection from loneliness, and theoretical approaches differentiating between social and emotional loneliness, suggest the importance of neighborhoods in preventing loneliness. This approach was used to test the influence of neighborhood factors on loneliness and the mediating role of social networks. Research Design and Methods: A questionnaire survey of 917 people aged 60–100 years was conducted in one region of Aotearoa/New Zealand to assess loneliness, social network types, social participation, marital status, gender, health, and four aspects of neighborhood perceptions. Results: Social and emotional loneliness scores were regressed on predicted demographic and social variables, followed by perceptions of Housing Satisfaction, Neighborhood Accessibility, Neighborhood Security, and Neighborhood Social Cohesion. Neighborhood variables added significant explanation of variance in both social and emotional loneliness. Mediation tests using PROCESS showed that the effects of all neighborhood variables were mediated by Private-Restricted or Locally Integrated Network types on Social Loneliness only. Discussion and Implications: These findings highlight the importance of neighborhood factors in relation to feelings of loneliness and the recognition of social network types as mediators of these relationships for social loneliness. The aspects of neighborhoods that prevent loneliness provide directions for planners and prevention programs. Interventions to prevent social loneliness can usefully and practicably focus on the housing and neighborhood environment.